1989
DOI: 10.1111/j.1399-0004.1989.tb03182.x
|View full text |Cite
|
Sign up to set email alerts
|

Mental illness and cognition in relation to age at puberty: a hypothesis

Abstract: Onset of puberty is usually considered to coincide with the last major step in brain development: the elimination of some 40% of neuronal synapses. Mean pubertal age has declined by some 4 years during the last 100 years. There is a relation between age at puberty and body build, and between body build and mental illness. The difference in body build between schizophrenia (S) and manic‐depressive psychosis (MDP) is similar to that between late and early maturers. It is suggested that S affects late‐maturing in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 56 publications
2
5
0
Order By: Relevance
“…This speculation is also consistent with the evolutionary psychiatric hypotheses proposed by Burns that schizophrenia emerged as a byproduct in the evolution of human social behavior [69] , by Stevens and Price that schizophrenia is an advantageous evolutionary phenotype playing the role of splitting a group when the population becomes too large [70] , and by Saugstad that the less clear cerebral lateralization in schizophrenia is associated with late, slow maturation of the cortex [71] . On the other hand, social isolation can also be stressful, which could generate an evolutionary pressure for an adaptation strategy against isolation.…”
Section: Schizophreniasupporting
confidence: 69%
“…This speculation is also consistent with the evolutionary psychiatric hypotheses proposed by Burns that schizophrenia emerged as a byproduct in the evolution of human social behavior [69] , by Stevens and Price that schizophrenia is an advantageous evolutionary phenotype playing the role of splitting a group when the population becomes too large [70] , and by Saugstad that the less clear cerebral lateralization in schizophrenia is associated with late, slow maturation of the cortex [71] . On the other hand, social isolation can also be stressful, which could generate an evolutionary pressure for an adaptation strategy against isolation.…”
Section: Schizophreniasupporting
confidence: 69%
“…[42][43][44][45][46][47][48][49][50] Questionnaire studies 51 have found no relationship between an overall "psychosis proneness" score and puberty timing, but some studies found a correlation between age at menarche and age at onset of symptoms. 42,52,53 Altered pubertal timing was not found in children who received a diagnosis of schizophrenia before age 12.…”
Section: Iq and Psychopathologymentioning
confidence: 99%
“…It is generally accepted that continuous variables: height, age at puberty (rate of maturation) are multifactorially inherited. The importance of environment in relation to adult height and pubertal age is clear when we consider the 13 cm increase in mean adult height and four years decline in pubertal age in the last 100 years, a phenotypic response to improved living conditions (high protein diet) in Western Industrialized countries (Saugstad, 1989c(Saugstad, , d, 1994a.…”
Section: Environmental Factors and Multi-factorial Inheritancementioning
confidence: 99%